El consentimiento informado en el sistema de seguridad social en salud (2020)
The Informed Consent in the social security health system has been given as a mechanism for informing doctors about patients, since it has been considered deficient, limited and imprecise causing with this a harmful result in the action of the doctor in relation to the procedures that can be applied to a patient. It is important to establish that informed consent allows the patient to have clear and precise and concise information about the diagnosis, procedure, and treatment Allowing with this that it is the one who decides whether or not to accept the above, the patient must have a clear understanding of their health condition and based on this, can make the relevant decisions. Currently in Colombia there is very poor normative and little regulation About informed. Law 23 of 1981 and Decree 3380 of 1981 determines the duty of medical action but they are not very precise to what is related to the CI What has caused that this has been obtained ineffectively currently, this process is handled by health care entities through preestablished formats that do not grant any type of specific information to the patient. In the practice of the medical act, it is not clear who is obliged to prepare and deliver the Informed Consent, which is why procedural inconveniences have been generated in Ethical Disciplinary investigations in the Medical Ethics Courts when the criminal or civil responsibility for the medical exercise. It is important to note that informed consent is the means of evidence that the doctor has for his defense, in the case of malpractice and medical ethics lawsuits, since it is enshrined in Law 23 of 1981 that the doctor does not perform any medical or surgical procedure without the the prior authorization of the patient.